Multicentre retrospective study of intravascular large B‐cell lymphoma treated at academic institutions within the United States. (1st May 2019) - Geer, Marcus; Roberts, Emily; Shango, Maryann; Till, Brian G.; Smith, Stephen D.; Abbas, Hashim; Hill, Brian T.; Kaplan, Jason; Barr, Paul M.; Caimi, Paolo; Stephens, Deborah M.; Lin, Emily; et al.
Summary: Intravascular large B‐cell lymphoma (IVLBCL) is a rare entity, with a generally aggressive course that may vary based on geographic presentation. While a United States (US) registry study showed relatively good outcomes with IVLBCL, clinicopathological and treatment data were unavailable. We performed a detailed retrospective review of cases identified at 8 US medical centres, to improve understanding of IVLBCL and inform management. We compiled data retrieved via an Institutional Review Board‐approved review of IVLBCL cases identified from 1999 to 2015 at nine academic institutions across the US. We characterized the cohort's clinical status at time of diagnosis, presenting diagnostic and clinical features of the disease, treatment modalities used and overall prognostic data. Our cohort consisted of 54 patients with varying degrees of clinical features. Adjusting for age, better performance status at presentation was associated with increased survival time for the patients diagnosed in vivo (hazard ratio: 2·12, 95% confidence interval 1·28, 3·53). Based on the data we have collected, it would appear that the time interval to diagnosis is a significant contributor to outcomes of patients with IVLBCL.